2020
DOI: 10.3390/f11040478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Steaming Mode on Chemical Characteristics and Colour of Birch Wood

Abstract: The aim of this work was to evaluate the changes of the chemical components in birch wood (Betula pendula Roth) caused by steaming with saturated steam at three temperatures—105 °C, 125 °C and 135 °C. In the samples of the original wood and wood after steaming, select chemical characteristics were determined, and wood, isolated holocellulose and Seiferts’s cellulose were analysed by attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. The greatest changes in the birch wood character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Lower temperatures (160 and 180 • C) caused less color changes in pH 6, 8 and 10 compared to acidic and water media, while high temperatures (200 • C) caused the most color changes. The hydrothermal treatment changed the color of the sample significantly as the treatment temperature increased [31][32][33]. This finding was consistent with the research findings in [34].…”
Section: Acidity Variation In Rubberwoodsupporting
confidence: 91%
“…Lower temperatures (160 and 180 • C) caused less color changes in pH 6, 8 and 10 compared to acidic and water media, while high temperatures (200 • C) caused the most color changes. The hydrothermal treatment changed the color of the sample significantly as the treatment temperature increased [31][32][33]. This finding was consistent with the research findings in [34].…”
Section: Acidity Variation In Rubberwoodsupporting
confidence: 91%
“…The changes in the colour of all wood species resulting from thermal modification by saturated water vapor are considered to be of a permanent nature and irreversible. The irreversibility of the changes in the colour of woods is confirmed by the differences in the lignin-carbohydrate complex of the TM wood, as well as native wood, and by the presence of monosaccharides, organic acids, and the basic structural elements of the guaiacyl-syringyl lignin in the condensate [ 1 , 4 , 5 , 6 , 7 , 8 ]. Irreversible changes in the colour of the TM wood expand the opportunities for the use of these four woods in the fields of construction-joinery, and construction art and design.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, alder ( Alnus glutinosa (L.) Gaertn), European beech ( Fagus sylvatica L.), Paper birch ( Betula papyrifera Marsh), and Norway maple wood ( Acer pseudoplatanus L.) were used. Samples of 15 × 100 × 250 mm 3 (radial × tangential × longitudinal) were prepared from both TM boards and unmodified (native) boards with saturated water vapour at a 135 ± 2.5 °C temperature for 6 h. The parameters for the modification process for the selected wood species are described in more detail in the works [ 4 , 5 , 6 , 7 ]. The samples were prepared from six-month air-conditioned and sanded boards (last sand grit P 180, sanded first in the transversely and following in the longitudinal direction).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syafinaz [8] studied the relationship between wood color and formaldehyde emissions from plywood of seven tropical hardwood species. Anton [9] determined the chemical properties of logs and wood samples after boiling, analyzed the wood, and isolated holocellulose and Sievetz cellulose by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). It was found that the qualitative and quantitative changes in hemicellulose extracts during the cooking of birch were closely related to the measured pH value and wood color.…”
Section: Introductionmentioning
confidence: 99%